2020
DOI: 10.17345/rio24.325-366
|View full text |Cite
|
Sign up to set email alerts
|

Presencia sindical y gestión de riesgos laborales de origen psicosocial. Un análisis del caso español

Abstract: La desregulación y precarización del mercado de trabajo ha derivado en un incremento de los riesgos y enfermedades de origen psicosocial en Europa en general, y en España en particular. Ante tal contexto, el objetivo de la presente investigación es evaluar el impacto de la representación sindical especializada (delegados de prevención) sobre la implementación de medidas de prevención de riesgos psicosociales en las empresas. A tal efecto, utilizamos la Segunda Encuesta Europea de Empresas sobre Riesgos Nuevos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…19 Since the 1980s, the two unions combined have accounted for more than two-thirds of the elected workers' representatives in Spain (in 2018: CCOO 35.7% and UGT 32.7%). 12…”
Section: Worker Representative Participation In Occupational Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Since the 1980s, the two unions combined have accounted for more than two-thirds of the elected workers' representatives in Spain (in 2018: CCOO 35.7% and UGT 32.7%). 12…”
Section: Worker Representative Participation In Occupational Healthmentioning
confidence: 99%
“…8 Prepandemic evidence focusing on occupational risk prevention has also shown that worker representative participation in workplaces has been related to higher implementation of the standards of the preventive management cycle (risk assessment, preventive planning, and implementation of preventive measures). [10][11][12][13] However, the pandemic has also made clear that the process of flexibilization of employment relations over the last decades has expanded precarious employment arrangements and has deteriorated the influence of organized labor, thus constraining the capacity of workers' representatives to act. 4,14…”
mentioning
confidence: 99%
“…Todos estos aspectos, como se ha visto, están asociados a un empleo más saludable y a la mejora de la calidad de vida en el trabajo y en la base de modelos de gestión laboral como la 2. Este artículo no se ocupa de la participación representativa que en el contexto europeo está basada en los derechos de los trabajadores y trabajadoras, reconocidos a través de la legislación y la negociación colectiva (Hyman y Mason, 1995;Pateman, 1970). Ello requeriría un contexto analítico totalmente distinto, el de las relaciones laborales, y en el que tendría sentido plantearse la distribución de poder, el cuestionamiento de la prerrogativa empresarial y la democracia en el trabajo.…”
Section: Prácticas Empresariales De Participación Directaunclassified
“…La evidencia en salud ocupacional muestra que donde existe representación sindicalizada de las trabajadoras, con poder colectivo y de perfil propositivo, la acción preventiva es más frecuente y tiene mejores resultados (Walters y Wadsworth, 2014;Ollé-Espluga et al, 2015;Hall et al, 2016;Janetzke y Ertel, 2017;Payà y Pizzi, 2020). Este fue el criterio que guio la selección de las tres empresas en las que se realizó el trabajo de campo, al que se sumó el de la accesibilidad.…”
Section: Métodosunclassified
“…13,21 Still, the role of workers' representatives could be significant. Evidence from the field of occupational health showed where there is unionized representation of workers, with collective power and a proactive approach, preventive action is more frequent and has better results, [91][92][93][94][95] also in relation to direct participation practices' implementation. 96,97 However, our analysis does not address representative participation, which, in the European Union, is based on workers' rights, recognized through legislation and collective bargaining.…”
Section: Limitations and Strengthsmentioning
confidence: 99%